LITERASI KEUANGAN DAN PEMAKAIAN KARTU KREDIT PADA PENDUDUK DKI JAKARTA GENERASI MILENIAL - Alvina, Patricia; Widyastuti, Arie (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2025)
The imbalance between the rise in basic commodity prices and the increase in income has forced a significant portion of the population to resort to borrowing in order to meet their living expenses. Credit cards have become the preferred pay-later payment method for the majority of the population due to the ease of transaction processes and the benefits associated with responsible usage. Unfortunately, there are still credit card users who lack proper knowledge of personal finance, leading to a substantial number of users ultimately failing to meet their financial obligations. This research investigates the relationship between financial literacy and the level of debt among millennial residents of Jakarta, Indonesia. Data processing techniques employed in this study involve correlation analysis and comparative analysis aimed at understanding the interplay between variables and identifying groups with superior financial literacy and/or debt levels. The findings of this study indicate a positive correlation between financial literacy and debt levels. Financial literacy is positively related to income, meaning that higher income levels are associated with greater financial literacy. Debt levels exhibit a negative relationship with gender, with women showing better debt management compared to men, and with income, where higher income levels are associated with better debt management.